A social history of the San of Tsholotsho district ward 7 and 10 from the colonial era to independence - 2017. - Ndlovu, Nomthandazo Kuthaba (Midlands State University, 2018)
This study focuses on the social life of the San people of Tsholotsho District ward 7 and 10 from the colonial era up to independence. The study seeks to bring to attention the plight of San people who as one of world’s oldest indigenous groups has consistently suffered domination, discrimination, cultural assimilation by other social groups. Their history has not been documented because they have never had any contact with technology and modernization they have been widely marginalised. These indigenous people and their cultures are under the threat of extinction, as they are subjected to economic and political marginalization. The research was largely qualitative and some of crucial information was gathered from primary sources through interviews. This research reveals the evils of colonialism on the indigenous people like San people whom they stereotyped and labelled as backward, barbaric and incapable of decision making. The study analyses how the colonialist politics of indirect rule and anti-hunting laws disturbed the San livelihoods. Chapter one looked at the origins of the San people and their settlements in Tsholotsho and their socio economic lives before the colonial era. Chapter two reviewed the strategies adopted by the government working with non-governmental organisations in improving their social life and modernising them, particularly wards 7 and 10. Chapter three of this study focused on the change and continuity of the San lives after 1980